A microphysics guide to cirrus – Part 2: Climatologies of clouds and humidity from observations - Krämer, Martina; Rolf, Christian; Spelten, Nicole; Afchine, Armin; Fahey, David; Jensen, Eric; Khaykin, Sergey; Kuhn, Thomas; Lawson, Paul; Lykov, Alexey; Pan, Laura L.; Riese, Martin; et al. (Atmospheric chemistry and physics, 2020)
This study presents airborne in situ and satellite remote sensing climatologies of cirrus clouds and humidity. The climatologies serve as a guide to the properties of cirrus clouds, with the new in situ database providing detailed insights into boreal midlatitudes and the tropics, while the satellite-borne data set offers a global overview. To this end, an extensive, quality-checked data archive, the Cirrus Guide II in situ database, is created from airborne in situ measurements during 150 flights in 24 campaigns. The archive contains meteorological parameters, ice water content (IWC), ice crystal number concentration (Nice), ice crystal mean mass radius (Rice), relative humidity with respect to ice (RHice), and water vapor mixing ratio (H2O) for each of the flights. Depending on the parameter, the database has been extended by about a factor of 5–10 compared to earlier studies. As one result of our investigation, we show that the medians of Nice, Rice, and RHice have distinct patterns in the IWC–T parameter space. Lookup tables of these variables as functions of IWC and T can be used to improve global model cirrus representation and remote sensing retrieval methods. Another outcome of our investigation is that across all latitudes, the thicker liquid-origin cirrus predominate at lower altitudes, while at higher altitudes the thinner in situ-origin cirrus prevail. Further, examination of the radiative characteristics of in situ-origin and liquid-origin cirrus shows that the in situ-origin cirrus only slightly warm the atmosphere, while liquid-origin cirrus have a strong cooling effect. An important step in completing the Cirrus Guide II is the provision of the global cirrus Nice climatology, derived by means of the retrieval algorithm DARDAR-Nice from 10 years of cirrus remote sensing observations from satellite. The in situ measurement database has been used to evaluate and improve the satellite observations. We found that the global median Nice from satellite observations is almost 2 times higher than the in situ median and increases slightly with decreasing temperature. Nice medians of the most frequently occurring cirrus sorted by geographical regions are highest in the tropics, followed by austral and boreal midlatitudes, Antarctica, and the Arctic. Since the satellite climatologies enclose the entire spatial and temporal Nice occurrence, we could deduce that half of the cirrus are located in the lowest, warmest (224–242 K) cirrus layer and contain a significant amount of liquid-origin cirrus. A specific highlight of the study is the in situ observations of cirrus and humidity in the Asian monsoon anticyclone and the comparison to the surrounding tropics. In the convectively very active Asian monsoon, peak values of Nice and IWC of 30 cm−3 and 1000 ppmv are detected around the cold point tropopause (CPT). Above the CPT, ice particles that are convectively injected can locally add a significant amount of water available for exchange with the stratosphere. We found IWCs of up to 8 ppmv in the Asian monsoon in comparison to only 2 ppmv in the surrounding tropics. Also, the highest RHice values (120 %–150 %) inside of clouds and in clear sky are observed around and above the CPT. We attribute this to the high H2O mixing ratios (typically 3–5 ppmv) observed in the Asian monsoon compared to 1.5 to 3 ppmv found in the tropics. Above the CPT, supersaturations of 10 %–20 % are observed in regions of weak convective activity and up to about 50 % in the Asian monsoon. This implies that the water available for transport into the stratosphere might be higher than the expected saturation value.